Broken kinship: Family property disputes and the common intention constructive trust in Singapore - TANG, Hang Wu (Institutional Knowledge at Singapore Management University, 2024)
There has been a proliferation of common intention constructive trust claims in Singapore. The main reason is that families have acquired real estate using their collective earning power without explicitly considering the individual entitlement of each family member. When a dispute arises, the claim is often pleaded as a common intention constructive trust. The complication with applying the law on the common intention constructive trust is that this is an English doctrine developed to deal with a different social context i.e. the breakdown of the relationship between cohabiting couples. In Singapore, the common intention constructive trust applies primarily in a different situation namely in the breakdown of kinship between parents and offsprings or between siblings. These relationships are often difficult to unpack because they are imbued with informal familial and cultural norms. Doctrinal complexity is also presented since the common intention constructive trust is often pleaded together with other doctrines such as resulting trusts and gifts. This article proposes that it is time to take Occam’s razor to the often cited six-steps framework in Chan Yuen Lan v See Fong Mun to a simplified three-stage analysis.